Tinjauan Hukum Islam Terhadap Praktik Hibah Hareuta Peunulang di Aceh - Munadi Usman (State Islamic University (UIN) of Sunan Ampel, 2020)
In Acehnese society, there is a tradition called hareuta peunulang, which is the practice of giving a number of assets to married girls in preparation for starting a new life with her husband. This practice is still often carried out until now, especially by people in the Pidie Regency, Aceh Besar District and parts of the West Aceh region. This practice seems to be gender-biased, which is more privileging girls and discriminating boys. This article wants to criticize the practice of hareuta peunulang grants using the theory of grants in Islamic law, with the aim of finding a contradiction between the two and offering several legal formulas to reconstruct these traditional institutions so that they are in line with the ideals of Islamic law.